2006
DOI: 10.1002/app.23899
|View full text |Cite
|
Sign up to set email alerts
|

Complex coacervation of the gelatin–poly(acrylic acid) system

Abstract: ABSTRACT:The system gelatin-poly(acrylic acid) (PAA) undergoes not only complex coacervation but also flocculation. The latter is incompatible with an encapsulation process. pH adjustment rate, ionic strength, temperature, and total macromolecular concentration have been studied to understand the origin of flocculation and to obtain a set of optimized parameters for coacervation using on-line turbidimetric titration. State diagrams were built, by varying gelatin/PAA mass ratio (R) and pH, for different PAA mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Based on the fitted values, f sol,core can be estimated as (1 − f sol,core )(4/3)π R core 3 = N agg ν core , where ν core is the PAGE block volume (Note that the volume of PAGE block is used to estimate the polymer volume in the cores because the volume of charged block in an aqueous solution is difficult to measure [41,47]). As expected, a large amount of water ( f sol,core ~ 0.8) is maintained inside the coacervate cores for the four C3Ms, which shows good agreement with previous results [61,62,63,64]. This reflects the fact that the cores of C3Ms are relatively hydrophilic compared to traditional hydrophobic-driven micelles.…”
Section: Resultssupporting
confidence: 91%
“…Based on the fitted values, f sol,core can be estimated as (1 − f sol,core )(4/3)π R core 3 = N agg ν core , where ν core is the PAGE block volume (Note that the volume of PAGE block is used to estimate the polymer volume in the cores because the volume of charged block in an aqueous solution is difficult to measure [41,47]). As expected, a large amount of water ( f sol,core ~ 0.8) is maintained inside the coacervate cores for the four C3Ms, which shows good agreement with previous results [61,62,63,64]. This reflects the fact that the cores of C3Ms are relatively hydrophilic compared to traditional hydrophobic-driven micelles.…”
Section: Resultssupporting
confidence: 91%
“…However, previous studies have indicated that coacervates with much lower charge densities, consisting for example of proteins and weakly charged polysaccharides, also consist of 80% water. 25,27,29,37 The current mean field theory predicts a much higher water content for charge densities of 20% for the same value of R. It is therefore not clear yet how such an apparently robust water content can be explained theoretically. Critical Salt Concentration.…”
Section: Resultsmentioning
confidence: 95%
“…Mathieu et al reported a water content of 70-80% for coacervates of gelatin and PAA. 37 Wang et al reported water contents ranging from 65% to 85% for coacervates of βlactoglobulin and pectin. 29 They found higher water contents when coacervates were prepared at lower protein to pectin ratios.…”
Section: Resultsmentioning
confidence: 99%
“…The system used so far is mainly gelatin-based capsule materials due to its natural non-toxic water-solubility and good film-forming property, such as gelatin/poly (acrylic acid) [25], gelatin/xanthan gum [26], gelatin/alginate [27], gelatin/carboxymethylcellulose [28] and gelatin/Arabic gum [29][30][31][32]. Among these materials, gelatin (GE)/Arabic gum (AG) has been widely used and extensively applied.…”
Section: Introductionmentioning
confidence: 99%